Development of Thin Film Amorphous Silicon Tandem Junction Based Photocathodes Providing High Open-Circuit Voltages for Hydrogen Production - F. Urbain; K. Wilken; V. Smirnov; O. Astakhov; A. Lambertz; J.-P. Becker; U. Rau; J. Ziegler; B. Kaiser; W. Jaegermann; F. Finger (International Journal of Photoenergy)
Hydrogenated amorphous silicon thin film tandem solar cells (a-Si:H/a-Si:H) have been developed with focus on high open-circuit voltages for the direct application as photocathodes in photoelectrochemical water splitting devices. By temperature variation during deposition of the intrinsic a-Si:H absorber layers the band gap energy of a-Si:H absorber layers, correlating with the hydrogen content of the material, can be adjusted and combined in a way that a-Si:H/a-Si:H tandem solar cells provide open-circuit voltages up to 1.87 V. The applicability of the tandem solar cells as photocathodes was investigated in a photoelectrochemical cell (PEC) measurement set-up. With platinum as a catalyst, the a-Si:H/a-Si:H based photocathodes exhibit a high photocurrent onset potential of 1.76 V versus the reversible hydrogen electrode (RHE) and a photocurrent of 5.3 mA/cm2 at 0 V versus RHE (under halogen lamp illumination). Our results provide evidence that a direct application of thin film silicon based photocathodes fulfills the main thermodynamic requirements to generate hydrogen. Furthermore, the presented approach may provide an efficient and low-cost route to solar hydrogen production.